INFLUENCE OF THE TRANSMITTED INFECTION OF COVID-19 ON THE PREVALENCE AND COURSE OF ATRIAL FIBRILLATION IN HOSPITALIZED PATIENTS - Sychov, O.S.; Stasyshena, O.V.; Mikhalieva, T.V.; Torbas, O.O.; Husarchuk, A.G. (World of Medicine and Biology, 2023)
The study was devoted to the analysis of heart rhythm and conduction disorders, namely atrial fibrillation in patients after a COVID-19 infection. 179 patients who were hospitalized from 09.20.2020 to 12.21.2021 were included in the screening. The main part of the study was made up of 116 people (64.8 %) with atrial fibrillation who suffered from a coronavirus infection. Group 1 was formed by 80 (69 %) patients who had AF before COVID-19. Group 2 – 36 patients (31 %) who had this arrhythmia after undergoing COVID-19. Control group – 49 patients with AF who had no history of COVID-19 infection. Other rhythm disturbances – 63 patients (35.2 %). Atrial fibrillation occurred more often than other heart rhythm and conduction disorders 64.5 % versus 35.2 % (p